Groundwater Study of Southwest Gwoza (Sheet 114) Borno State, Nigeria - S. Adamu; M. V. Joseph; M. Bukar (Arid Zone Journal of Engineering, Technology and Environment, 2012)
Hydrogeological mapping and water chemistry of Gwoza South-West (topographical sheet 114) of the crystalline basement complex at the foot of Mandara Hills in North-Eastern Nigeria was carried out. Rainfall data was collected from the area for a period of 16 years. Water table configuration map and direction of groundwater flow was produced. Chemical analyses and physical parameters of the water was determined using spectrophotometer, flame photometer, ph meter, and electrical conductivity meter. Semi urban water consumption per family per capita per day was determined using 20 households. A total of nine major ions (Ca2+, Na+, K+, Mg2+, Cl-, S042-, N02- and HC03-) were analyzed. Results of the study indicate that the area experiences a moderately average rainfall of about 743mm per annum, depth to water table ranged between 2.6 – 18.8m and 0.1 – 18.2m at the peak of dry season and rainy season respectively and per capital daily water consumption per family, ranged from 9 litres to 76 litres. The values of major ions present in water indicate that it is fit for both human and animal consumption as they fall within WHO (1996) standard. Demand for water is highest in the dry season, when recharge is poorest.